Improvement of in-field performance for EuBCO with heavily doped BHO coated conductors by PLD method with high temperature deposition and low temperature annealing. Issue 1 (March 2020) - Ibi, A; Machi, T; Nakaoka, K; Sato, M; Izumi, T; Nishimura, J; Miura, M; Yokoe, D; Kato, T; Hirayama, T
Abstract: Recently, we have found that BaHfO3 (BHO)-doped EuBa2 Cu3 O7-X (EuBCO) coated conductors by the combination of the IBAD and PLD methods show high critical current ( Ic ) even in an applied magnetic field. However, for the wide application of BaMO3 (BMO, M: metal)-doped REBa2 Cu3 O7-X (REBCO) coated conductors to industrial and commercial applications, much higher in-field performance is required. It is known that the critical temperature ( Tc ) of BMO-doped REBCO layers, especially by the PLD method, decreases with the increase in the amount of doped BMO apparently due to the strain of the REBCO induced by BMO doping. Therefore, it is difficult to improve the critical current density ( Jc ) in the applied magnetic field of BMO doped REBCO coated conductors only by increasing the quantity of BMO especially at high temperatures such as 77 K. To solve this problem, we tried to optimize the deposition conditions, especially the deposition temperature and O2 annealing processes for heavily BHO doped-EuBCO layers fabricated by the PLD method. As a result, the combination of high temperature deposition and low temperature O2 annealing was effective in obtaining high Tc and high in-field performance of heavily BMO-doped REBCO coated conductors. The Tc of 10 mol% BHO-doped EuBCO coated conductors was 93.9 K (setting a deposition temperature of 1150 ° C and O2 annealing temperature of 280 ° C) which is nearly the same as that for non-doped EuBCO coated conductors. On the other hand, overdoping is preferred for high in-field Jc . Therefore, a high Jc under a magnetic field was obtained in the BMO-doped REBCO layer annealed at a low temperature. The Jc (min.) of 5 mol% BHO-doped EuBCo coated conductors was 0.62 MA/cm 2 at 77 K and 3 T (setting deposition temperature of 1150 ° C and O2 annealing temperature of 250 ° C). Using these results, we confirm the successful fabrication of heavily BHO-doped EuBCO coated conductors showing high in-field performance by the PLD method.